Biochemistry for dummies - Moore, John T. 4 0 16; Langley, Richard; 5 (Hoboken, N.J. : Wiley Publishing, 2011)
A comprehensive guide to biochemistry that covers basic concepts of water and organic chemistry, proteins, carbohydrates, lipids, acids, bioenergetics, DNA, and related topics; provides figures that illustrate biochemical structures and real-world examples that connect biochemical concepts to everyday life; and includes information on careers in biochemistry, and other related topics.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Biochemistry. -- 20; 20; 2